Harmonizing the Authority of Fishery Resources Management in the Era of Regional Autonomy Based on Pancasila - Mashuril Anwar; Maya Shafira; Sunarto Sunarto (Fakultas Hukum Universitas Lampung, 2020)
The configuration of fisheries policy before regional autonomy shows the hegemony of the country which adheres to the legal doctrines of collective ownership, centralism, and anti-pluralism. Since the era of regional autonomy, the provincial and district / city governments have had more coherent authority in managing their regional potential, including fishery resources. With the shift in authority in managing fishery resources, it is hoped that the regions can play a role in optimizing the utilization of fisheries potential. But on the other hand, optimal management of fishery resources is difficult to achieve without harmonious policies. Therefore, to prevent conflicts of interest in the fisheries sector, Pancasila values need to be revived in fisheries resource management policies. The problems studied in this study are the authority of local governments in managing fishery resources in the era of regional autonomy, problems of harmonizing local government authority in managing fisheries resources, and harmonizing local government authority in managing fisheries resources based on Pancasila values. By using a normative juridical approach, the results of the research show that the authority of the regional government in managing fishery resources in the era of regional autonomy includes authority in the capture fisheries sector, authority in the field of cultivation, authority in the field of supervision of marine and fishery resources, and authority in the field of processing and processing. fishery marketing. However, so far there have been various disharmony problems with local government authorities in managing fishery resources. In addition, although regional autonomy is believed to have various advantages in optimizing the potential of natural resources, the management of fishery resources carried out in the era of regional autonomy has not fully animated the values of Pancasila as the philosophy of the Indonesian nation.